Engaging the Crowd: Social Movement Building via Online Bystander Mobilization - Siddarth, Divya; Pal, Joyojeet (ICTD 2020, 2020)
Social media has become increasingly important as a space for both organized and ad-hoc activism. As social movement organizations have shifted many aspects of their communication online, bystander populations - citizens who may be somewhat interested in a movement but are largely uninvolved in its activities - have begun to play a more significant role in the achievement of movement aims. In this paper, we examine bystander targeting on social media by social movement organizations in India. Through interviews, observation, and participation, we investigate ways that activists themselves conceptualize, carry out, and reflect upon their own messaging strategies in online spaces, and the perceived success and failure of these strategies. We discuss the limitations of social media as a space in which to achieve movement aims, particularly in a class-segregated context. Our work illustrates the tension faced by activists between prioritizing short and long-term movement goals in the digital sphere.